2002
DOI: 10.1046/j.1365-2222.2002.01281.x
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral blood CD4+ and CD8+ T cell type 1 and type 2 cytokine production in atopic asthmatic and normal subjects

Abstract: The frequencies of peripheral blood CD8+ T cells producing type 1 and type 2 cytokines are comparable with the frequencies of CD4+ T cells. There was an increased frequency of IFN-gamma producing CD4+ and CD8+ T cells in asthmatic compared with normal subjects. Further studies investigating T cells derived from the airways and investigating various stages within the disease process are required to further elucidate the importance of type 2 and type 1 T cell cytokine production in the pathogenesis of human alle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
43
1
2

Year Published

2003
2003
2008
2008

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 43 publications
10
43
1
2
Order By: Relevance
“…Thus, IFN-c-producing Th1-type cells detected in peripheral blood of atopic patients have been suggested to also play a role in asthma [35,36], especially during the symptomatic phases of the disease. It could be hypothesised that a Th2 orientation in asthma mainly characterises the immune response during the sensitisation process and the acute reaction to allergen exposure; whereas, chronic inflammation could be underlined by a less specific T-cell profile.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, IFN-c-producing Th1-type cells detected in peripheral blood of atopic patients have been suggested to also play a role in asthma [35,36], especially during the symptomatic phases of the disease. It could be hypothesised that a Th2 orientation in asthma mainly characterises the immune response during the sensitisation process and the acute reaction to allergen exposure; whereas, chronic inflammation could be underlined by a less specific T-cell profile.…”
Section: Discussionmentioning
confidence: 99%
“…Most infections induce asthma exacerbation and a T helper (Th) 1 inflammatory response. Some studies have shown that some Th1 cells are present in asthmatic patients, which could be related to bronchial hyperreactivity (Krug et al 1996;Magnan et al 2000;Cho et al 2002). Interferon-c (IFN-c), produced by Th1 cells, exerts an inhibitory effect on Th2 cells and has extensive and diverse immunoregulatory effects on various cells (Chung and Barnes 1999).…”
Section: Introductionmentioning
confidence: 99%
“…ϩ T cells can produce many cytokines, including IFN-␥, as well as IL-4 and IL-5, after induction (24,51), and a classification of these CD8 ϩ cells into a Tc1 subset (producing Th1-like cytokines) and a Tc2 subset (producing Th2-like cytokines) has been proposed (26).…”
Section: Discussionmentioning
confidence: 99%